Environmental Impact Assessment (EIA) and South African courts' interpretation of the legislative framework - van Eeden, Kathinka (Department of Public Law, 2023)
The debate on the issue of the submission of environmental impact assessments (EIAs) goes back to the 1970s. The value of EIAs was first recognised by the South African government in 1976 with a report by the-then South African Council for the Environment entitled Identification and Evaluation of the Effects of Development Projects on the Environment and in 1980 with the publication of the White Paper on a National Policy regarding Environment Conservation. The White Paper formed the basis for the Environment Conservation Act (ECA) 73 of 1989, which included some provisions for EIAs.